KETERLIBATAN PEREMPUAN DALAM AKTIFITAS EKONOMI HIJAU (STUDI KASUS DI WATES KOTA MAGELANG) - Sukarniati, Lestari (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2014)
Economic development should be done in conjunction with the improvement of the quality of the environment and reduce pollution so that poverty, malnutrition, and lack of access to clean water and food shortages can be overcome. Application of the principles of green economy is essential for creating sustainable development, but a lot of things faced by many countries to create the conditions. Defi ned as the green economy âas an economic environment that Achieves low carbon emissions , resource effi ciency and at the same time is socially inclusiveâ the study, entitled the involvement of women in economic activity green aims to look at the relationship between the environment and an understanding of the educational level of womenâs involvement in economic activity towards the green. The data used is primary data from 33 housewives. The results showed no correlation between environmental understanding and education with involve in green economic activities.